2012
DOI: 10.1530/joe-12-0057
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic transcriptional regulation of autocrine/paracrine igfbp1, 2, 3, 4, 5, and 6 in the skeletal muscle of the fine flounder during different nutritional statuses

Abstract: The IGF-binding proteins (IGFBPs) play a dual role in the regulation of the activity and bioavailability of IGFs in different tissues. Diverse evidence has shown that IGFBPs can inhibit and/or potentiate IGF actions. In this study, igfbp1, 2, 3, 4, 5, and 6 were isolated in the fine flounder, a flat fish species that shows slow growth and inherent Gh resistance in muscle. Subsequently, the expression of all igfbps was assessed in the skeletal muscle of flounder that underwent different nutritional statuses. ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 64 publications
9
43
2
Order By: Relevance
“…Conversely, effects of genistein on expression of igfbps likely reflect regulation by estrogen receptor-independent mechanisms since the pattern of regulation does not reflect treatment estrogenicity. Although roles of IGFBPs in fish muscle remain to be fully characterized, increased expression of igfbp4 and igfbp5b1 are correlated with periods of refeeding and growth (Gabillard et al, 2006;Bower et al, 2008;Safian et al, 2012;Cleveland and Weber, 2014b) or anabolic conditions in cell culture (Bower and Johnston, 2010b), suggesting these proteins promote anabolic activity in salmonid muscle. In mammals the growthpromoting effects of IGFBP5 are attributed to its high binding affinity for the extracellular matrix, which reduces its affinity for IGF1 and IGF2 by approximately 15-fold, possibly potentiating the binding of the IGF peptides to IGF receptors on the cell surface (Clemmons, 1998;Duan and Xu, 2005).…”
Section: Effects In Musclementioning
confidence: 99%
“…Conversely, effects of genistein on expression of igfbps likely reflect regulation by estrogen receptor-independent mechanisms since the pattern of regulation does not reflect treatment estrogenicity. Although roles of IGFBPs in fish muscle remain to be fully characterized, increased expression of igfbp4 and igfbp5b1 are correlated with periods of refeeding and growth (Gabillard et al, 2006;Bower et al, 2008;Safian et al, 2012;Cleveland and Weber, 2014b) or anabolic conditions in cell culture (Bower and Johnston, 2010b), suggesting these proteins promote anabolic activity in salmonid muscle. In mammals the growthpromoting effects of IGFBP5 are attributed to its high binding affinity for the extracellular matrix, which reduces its affinity for IGF1 and IGF2 by approximately 15-fold, possibly potentiating the binding of the IGF peptides to IGF receptors on the cell surface (Clemmons, 1998;Duan and Xu, 2005).…”
Section: Effects In Musclementioning
confidence: 99%
“…In addition, IGFBP-4 knockout mice show reduced prenatal growth (Ning et al, 2008). More recent studies have shown that IGFBP-5 plays a key role in muscle growth and differentiation (Mukherjee et al, 2008;Duan et al, 2010;Safian et al, 2012). However, IGFBP-5 knockout mice had no obvious abnormalities in muscle development, probably due to the compensatory effects of other IGFBPs (Ning et al, 2007).…”
Section: Developmental Expression Of Igfbpsmentioning
confidence: 99%
“…However, in rainbow trout, IGFBP-2 displayed no effect of starvation followed by a peak of mRNA abundance after 7 days of refeeding in liver, whereas starvation led to a decrease of the IGFBP-2 mRNA level in muscle (Gabillard et al 2006). Recently, the similar result was observed in the muscle of fine flounder, IGFBP-2 mRNA levels decreasing during fasting and returning to basal level during long-term refeeding (Safian et al 2012). To better understand the actions of IGFBP-2 in fish growing axis, in the present study, we investigated the mRNA expression levels of goldfish IGFBP-2 in hypothalamus, pituitary and liver tissues of goldfish under the condition of feeding, fasting and refeeding, respectively.…”
Section: Discussionmentioning
confidence: 60%
“…Over the past few years, IGFBP-2 cDNA had been cloned and characterized in many fish species, including zebra fish (Danio rerio) (Duan et al 1999;Zhou et al 2008), goby (Gillichthys mirabilis) (Gracey et al 2001), gilthead sea bream (Sparus aurata) (Funkenstein et al 2002), common carp (Cyprinus carpio) ), yellowtail (Seriola quinqueradiata) (Pedroso et al 2009), orange-spotted grouper (Epinephelus coioides) (Chen et al 2010), chinook salmon (Oncorhynchus tshawytscha) (Shimizu et al 2011), Atlantic croaker (Micropogonias undulatus) (Rahman and Thomas 2011), fine flounder (Paralichthys adspersus) (Safian et al 2012) and Japanese flounder (Paralichthys olivaceus) (Zhang et al 2013). Together these results, it shows that the structure of fish IGFBP-2 is conserved with highly degree to their mammalian counterparts, suggesting its conserved functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation